2015
DOI: 10.1089/jamp.2013.1104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Exhaled Particles from the Human Lungs in Airway Obstruction

Abstract: Airway obstruction does not change the number flux or size distribution of particles in exhaled breath. The high intersubject variability of particle emission supports the concept of online determination of aerosol properties (primarily number flux, during exhaled breath) during breath condensate sampling to properly normalize the results of biochemical analysis. As high dilution and variable dilution are the main challenges of biomarker assessment in exhaled breath condensate, this normalization procedure wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 24 publications
(30 reference statements)
2
46
0
6
Order By: Relevance
“…The mass median aerodynamic diameter of exhaled particles during sampling is between 0·7 and 1·5 μm (unpublished data) from P. Larsson and A‐C. Olin while the particle number concentrations have a broad maximum between 0·4 and 0·6 μm (Holmgren et al ., ; Schwarz et al ., ). An ultrasonic flow meter (OEM flow sensor, Spiroson‐AS, Medical Technologies, Zürich, Switzerland) measures exhaled flow and the exhaled volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass median aerodynamic diameter of exhaled particles during sampling is between 0·7 and 1·5 μm (unpublished data) from P. Larsson and A‐C. Olin while the particle number concentrations have a broad maximum between 0·4 and 0·6 μm (Holmgren et al ., ; Schwarz et al ., ). An ultrasonic flow meter (OEM flow sensor, Spiroson‐AS, Medical Technologies, Zürich, Switzerland) measures exhaled flow and the exhaled volume.…”
Section: Methodsmentioning
confidence: 99%
“…Test subjects inhaled particle-free air through a HEPA filter and exhaled into the PExA â instrument via a two-way valve that could direct the flow into the instrument or to ambient air. The mass median aerodynamic diameter of exhaled particles during sampling is between 0Á7 and 1Á5 lm (unpublished data) from P. Larsson and A-C. Olin while the particle number concentrations have a broad maximum between 0Á4 and 0Á6 lm (Holmgren et al, 2010;Schwarz et al, 2015). An ultrasonic flow meter (OEM flow sensor, Spiroson-AS, Medical Technologies, Z€ urich, Switzerland) measures exhaled flow and the exhaled volume.…”
Section: Particle Measurement and Samplingmentioning
confidence: 99%
“…L'identification de différents phénotypes de BPCO, reflétant les anomalies génétiques et cellulaires prédominantes dans la survenue de la BPCO chez chaque patient, est un des défis actuels dans le cadre du concept émergent de traitement personnalisé. À cet égard, le développement de nouvelles méthodes d'évaluation de l'inflammation, comme les expectorations induites, l'analyse des condensats d'air exhalés (à l'aide de nez électronique par exemple) et de nouveaux marqueurs (pH, leucotriène B4, prostaglandines, cytokines) paraît intéressant pour différencier ces différents phénotypes (Tableau 2) [99][100][101][102][103].…”
Section: Approches Génétiquesunclassified
“…With every single exhalation a human lung emits an aerosol, which contains small droplets of alveolar lining fluid (ALF) [1,2,3,4,5,6]. Although the mechanisms responsible for droplet formation are still unclear, the most probable one is associated with the processes of closure and reopening of the airways during normal breathing [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…During the subsequent inhalation the rupture of the fluid film is accompanied by droplet formation. The studies of the concentration and size distribution of aerosols [1,2,3,4,5,6] have demonstrated that an exhaled air of a healthy human during normal breathing contains, on average, a few submicron particles per cubic centimeter. In spite of the high reproducibility of measurements within subject, both characteristics show a high inter-subject variability and a strong dependence on the type of breathing and the breathing maneuvers before sampling [5,6].…”
Section: Introductionmentioning
confidence: 99%